FORMULA ENTERAL FUNGSIONAL “NEBULA”: KARAKTERISTIK VISKOSITAS, MUTU ORGANOLEPTIK, DAN KOMPOSISI GIZI BERBASIS BUAH NAGA MERAH, OAT DAN BUNGA TELANG - Fahmi, Muhammad Izzul Widad; Judiono; Fauziyah, Roro Nur; Putri, Azzahra Nadya (Jurnal Gizi dan Dietetik, 2025)
Enteral formula is a recommended nutritional intervention for patients with diabetes mellitus who are unable to achieve adequate oral intake. However, selecting ingredients with a low glycemic index and high fiber content is essential to prevent worsening hyperglycemia. This study aimed to evaluate the viscosity, organoleptic characteristics, and nutritional composition of the “NEBULA’’ enteral formula based on red dragon fruit, oat flour, and butterfly pea flower as an alternative diet for type 2 diabetes mellitus. A completely randomized design was used with three formulations: F1 (1:1:0.06), F2 (0.8:1.1:0.06), and F3 (1.5:0.8:0.06). Viscosity and organoleptic tests were conducted at the Organoleptic Laboratory, Poltekkes Kemenkes Bandung, while nutritional composition was calculated using the Indonesian Food Composition Table and proximate analysis. Viscosity was measured using the dynamic method, and organoleptic evaluation was performed with a hedonic test involving 33 semi-trained panelists. The results indicated that F2 and F3 met acceptable viscosity ranges, whereas F1 did not. Kruskal–Wallis analysis (p>0.05) showed no significant differences among formulations in color, taste, aroma, texture, or overall acceptability. Formula F2 exhibited the highest acceptance score. Proximate results were consistent with food composition calculations and fulfilled recommended criteria for diabetes mellitus. In conclusion, the NEBULA enteral formula demonstrates suitable physical quality and nutritional composition and has potential as an alternative nutritional option for individuals with type 2 diabetes mellitus.